Dynamic Performance Analysis of a Curved Cable-Stayed Bridge Based on the Direct Method and the Sensitivity-Based Iterative Method - Guanzhe Fa; Leqia He; Luigi Fenu; Bruno Briseghella (Advances in Civil Engineering)
Curved cable-stayed bridges have been regularly accepted due to their ability to cross long spans, and a number of studies have been conducted to investigate the mechanical or dynamic performance of them. Meanwhile, currently just a few studies focus on the curved composite cable-stayed bridges. In this study, an operational modal testing and finite element model updating of a conventional straight bridge with the steel-concrete composite girder were conducted to investigate the performance of the potential methods for the model updating, which included the direct method and the sensitivity-based iterative method. Then, dynamic tests were performed for one typical curved steel-concrete composite cable-stayed bridge as the key case study. A highly refined finite element model of the bridge was developed and then calibrated based on the aforementioned methods in reference to the experimental results. Finally, the dynamic behavior of the curved steel-concrete composite cable-stayed bridge was studied based on the model. It is found that the solution accuracy of the finite element model can be improved significantly by employing the structural health monitoring technique. Moreover, by using the iterative method, the solutions of the updating parameters are generally more accurate compared with the solutions of the direct method. Nevertheless, when the appropriate choices are made for the algorithmic parameters, both methods can lead to the updated models with satisfactory numerical analysis results as compared to the experimental data.